Вы находитесь на странице: 1из 3

Calculus Review for PDE

Amir Vig
In PDE, we will study (second order) equations of the form F (u, Du, D2 u, x) = 0. Here F :
2
R Rn Rn Rn R is a function that depends on the function u, gradient
u
x1
u
x1

Du = u = .
..

(1)

u
x1

the Hessian matrix

D 2 u = 2 u =

2u
x1 x1

..
.

2u
xn x1

...
..
.
...

and the independent variable x Rn . When we say F


on first order derivatives. When we say F depends on
order derivatives (not necessarily the whole matrix). If
x, we say that the PDE is linear. These will constitute
quarter (because nonlinear PDE are hard).

2u
x1 xn

..
.

2u
xn xn

(2)

depends on Du, we mean that it depends


D2 u, we mean that it depends on second
F is linear in all variables except perhaps
the majority of what we study in the first

Ok, so now we need to clarify some things: Suppose we have a function u(x, t) that takes in
one space variable x and one time variable t. It is really important to understand what do we mean
by expressions like ux (x, t) or ut (x, t). Here, x and t show up in two places... once as a subscript
and once as a variable the function u takes in. Are they the same? The answer is NO! ux simply
means the derivative of u with respect to the first variable... having nothing to do with where the
function is being evaluated. For example, you could have uxt (y, t + s + h) which is the derivative of
u in the first variable and then the second variable, evaluated at the point (y, t + s + h). Oftentimes,
people get confused by using the same letter for the variable which we differentiate with respect
to and the variable that u takes in... but they are different. However, when we do use the same
letter, ux (x, t) is the function u differentiated with respect to the first variable, evaluated at the
point (x, t). The x in the subscript is just indicating where the derivative is being taken, not where
this new function is being evaluated. Hopefully this is clear... Now, some more concrete things.
Chain Rule: Suppose u : Rn R is a function of m variables x1 , . . . , xm which takes values
in R. Now suppose f1 , . . . , fm : Rn R are m different functions which take in x = (x1 , . . . , xn ).

When you concactenate the functions, they form a vector: i.e.

f1 (x1 , . . . , xn )

..
f (x) =

(3)

fm (x1 , . . . , xn )
with m components. Hence, it makes sense to consider the composition u(f (x)). Note that u f :
Rn Rm R. So the composition takes in n variables and outputs a single number. The chain
rule from calculus tells us that
D(u f ) = Du Df = DuDf

(f1 )x
 . 1
= ((u f )x1 , . . . , (u f )xn ) = ux1 . . . uxm ..

(4)
...
..
.
...

(fm )x1

(f1 )xn
..
.

(5)

(fm )xn

Usually for us, we want to understand something like x1 u f (x), which is the first entry of the
above vector (when you multiply the matrices, you end up with a row vector). Taking the matrix
product and equating components of the above vectors gives
n
X

x1 (u f )(x) =

uxi (fi )x1 (x)

(6)

You can obviously replace x1 with any one of the other xj . Lets see an example. Suppose u : R3
R be given by u(f1 , f2 , f3 ) = f1 + f25 + f37 . Let f1 (x, y) = x3 , f2 (x, y) = xy 2 and f3 (x, y) = sin(x2 y).
Here m = 3 and n = 2. Then we have
u f1
u f2
u f3
+
+
f1 x
f2 x
f3 x
= 1 3x2 + 5f24 (x, y) y 2 + 7f36 (x, y) 2x cos(x2 y)

x u(f1 (x, y), f2 (x, y), f3 (x, y)) =

2 4

= 3x + 5(xy ) y + 7 sin(x y) 2x cos(x y)

(7)
(8)
(9)

We will use this quite a bit, so try to make sure you understand it.
Improper Integrals Suppose we have an arbitrary function u : R R which depends on x.
Suppose u is continuous... then the FTOC guarantees the existence of an antiderivative by the
formula
Z x
F (x) =
u(t) dt
(10)
0

Now imagine we have a more complicated integral like


Z

x3

G(x) =

u(t) dt

(11)

x2

How do we differentiate G in x? Well, an easy way to think about this is in terms of the FTOC...
We dont need to know what the antiderivative F is explicitly, but we can use the fact that it exists
2

to differentiate G. Here is how:


G(x) = F (x3 ) F (x2 ) = G0 (x) = F 0 (x3 ) 3x2 F 0 (x2 ) 2x
3

= u(x ) 3x u(x) 2x

(12)
(13)

where we used the one variable chain rule in the first line. The general formula is easily obtained
from this
Z b(x)
u(t) dt = u(a(x)) a0 (x) u(b(x)) b0 (x)
(14)
a(x)

We will use this quite a bit as well. For example today, we used the mass conservation law
Z
M = const. =

b+ch

u(x, t) dx =
0

u(x, t + h) dx

(15)

ch

Differentiating with respect to b gives


0 = u(b, t) = u(b + ch, t + h)

(16)

Now, differentiating with respect to h gives


0 = ux (b + ch, t) c + ut (b + ch, t + h)

(17)

Setting h = 0 gives the PDE cux (b, t) + ut (b, t) = 0. Notice that we used the letter b here, but b
could be any point (so we might as well call it x)... Recall x in the subscript ux has nothing to do
with either b or the actual input x!!! The PDE is more compactly written as cux + ut = 0.